Alternatif Perancangan Pondasi Tiang Pancang Jembatan Maros : Jalur Akses Menuju Stasiun Kereta Api Maros II - Salsa Purmadani Fatia; Syahrul Sariman; Eka Yuniarto (Jurnal Penelitian Teknik Sipil Konsolidasi, 2026)
This research discusses the alternative design of pile foundations on the Maros Bridge, as an access route to the Maros II Railway Station. In the existing foundation condition used is the bored pile type with a total of 18 piles for each abutment, which has a bearing capacity of 1038.02 kN (abutment 1) and 1400.18 kN (abutment 2) with a diameter of 0.8 m respectively. This alternative pile foundation design considers the comparison of the number, depth, and diameter of the foundation to achieve adequate bearing capacity and determine the shifts that occur using the Displacement Method. Based on the results of the design of the pile foundation design requires 22 piles with a diameter of 0.5 m for each abutment, with a pile foundation depth of 7 m at abutment 1 and 12 m at abutment 2 and with a horizontal shift value (Hi) 968.38, vertical (Vi) 2501.66, and moment (Mi) 3939.02. The bearing capacity of a single pile obtained is 788.3 kN for abutment 1 and 1278.52 kN for abutment 2, so the total bearing capacity that can be borne by the entire foundation in carrying the load of the upper structure has met the required requirements. The configuration of the existing bored pile foundation is 18 piles, while the alternative configuration plan results in a pile configuration of 22 piles with planned dimensions that are able to withstand the loads and forces acting on the bridge even though it requires a larger number of piles compared to the existing bored pile foundation.